2015
DOI: 10.4103/0300-1652.149167
|View full text |Cite
|
Sign up to set email alerts
|

Cervical cancer screening in women referred to healthcare centres in Tabriz, Iran

Abstract: Background:Cervical cancer is the second most common cancer among Iranian women and among the few cancers that could be easily diagnosed in the pre-malignant stage. We aimed to assess the status of cervical cancer screening in women referred to health care centres in Tabriz, northwest Iran.Materials and Methods:This descriptive-analytical study was done on 441 women referred to health care centres of Tabriz, northwest Iran. The centres were selected using the multi-stage cluster sampling method. The participan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
13
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(14 citation statements)
references
References 13 publications
1
13
0
Order By: Relevance
“…11 This was done free of charge in health care centers, but unfortunately test uptake was not favorable. In a recent Iranian study, 49.4% of females had done the test once in their lives, 10 whereas in other countries have reported rates of 85%–93%. 12 However, the results of previous studies showed a low level of performance and variations in breast cancer screening among Iranian females.…”
Section: Introductionmentioning
confidence: 96%
See 1 more Smart Citation
“…11 This was done free of charge in health care centers, but unfortunately test uptake was not favorable. In a recent Iranian study, 49.4% of females had done the test once in their lives, 10 whereas in other countries have reported rates of 85%–93%. 12 However, the results of previous studies showed a low level of performance and variations in breast cancer screening among Iranian females.…”
Section: Introductionmentioning
confidence: 96%
“… 8 Iran’s national breast cancer-screening program was introduced in 2012, and recommended that females >40 years have an annual mammogram, females 20–40 years old have one clinical breast examination (CBE) every 3 years and annual CBEs after 40 years, and monthly breast self-examination (BSEs) for females >20 years. 9 The Pap smear test is an effective screening program, 10 and according to the national program cervical cancer screening should be done for all females after marriage, and after three normal Pap smear samples this test should be repeated every 3 years. 11 This was done free of charge in health care centers, but unfortunately test uptake was not favorable.…”
Section: Introductionmentioning
confidence: 99%
“…While only 20%of the woman the mass media for early detection of the cervical cancer. As regarding after counseling cervical cancer protective practice in both groups, table (6) showed that a significant difference was observed related to Pap smear (p = .001). Also this table shows a highly statistical significant difference was observed for take vac-…”
Section: Sitting For Pap Smear Proceduresmentioning
confidence: 91%
“…cine, vaginal hygiene care, Self-examination for vulva, use of contraceptive as prescribed and diet rich in fresh vegetables and fruits(p =.0001). (6) showed that the women barriers to Pap smear test included the lack of knowledge, painful test, and male screening doctor ,fear of the results ,embarrassment ,costs, and lack of time.…”
Section: Control Groupmentioning
confidence: 99%
See 1 more Smart Citation